Development of an efficient high-performance thin layer chromatography method for determination of jasmonic acid in leaf tissue of Stevia rebaudiana (Bertoni) Bertoni. Issue 14 (18th July 2017) - Kilam, Divya; Saifi, M.; Agnihotri, A.; Abdin, M. Z.
Abstract: Determination of endogenous levels of jasmonic acid (JA) is essential, as it plays a pivotal role in the physiological processes during a plant's life cycle. A high performance thin layer chromatography (HPTLC) method was developed for the detection and quantification of JA in leaf extracts of medicinal plant, Stevia rebaudiana (Bertoni) Bertoni . The separation was achieved using the solvents ethyl acetate–benzene (1:1, v/v) as the mobile phase, followed by scanning and quantification at 295 nm. Densitometric analysis of leaf extract resulted in compact spots for JA at R f  = 0.45 ± 0.02. The linear regression analysis showed good relationship with r value. The recovery rate of JA indicated good reproducibility and repeatability of the assay. The statistical analysis proved the reproducibility of the method; therefore, it can be employed for routine quantification of JA in different tissue samples of S. rebaudiana and may also be extrapolated to other biological samples. Abstract :